2023
DOI: 10.1021/acs.energyfuels.2c03824
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions for Applications of Bio-Oils in the Asphalt Industry: A Step to Sequester Carbon in Roadway Infrastructure

Abstract: The global emphasis on sustainability and net zero carbon roads combined with the increased cost of crude oil has necessitated the application of new environmentally friendly alternatives to the bitumen used in asphalt by the pavement industry. Physical aging, chemical aging, and moisture damage are three important matters encountered in the pavement industry that are harmful for asphalt; bio-oils can decelerate the rates of physical aging and chemical aging in virgin bitumen, and bio-oils can substantially im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 206 publications
(398 reference statements)
0
10
0
Order By: Relevance
“…Moisture damage is a widespread concern among researchers and is also the main factor hindering the application of bio-asphalt in the road field. Especially in bio-regenerated asphalt, although bio-oil can restore the rheological properties of aged asphalt, it does not mean that it has a positive effect on the ability of asphalt to resist moisture damage and even makes the asphalt very susceptible to moisture damage. The moisture damage of bio-oil is usually related to its acidic component, polarizability, and water-soluble components, which leads to an increase in the moisture sensitivity of bio-asphalt, resulting in the failure of the adhesion and cohesion of the asphalt mixture . Oldham et al reduced acidic compounds in waste cooking oil through transesterification, significantly reducing its ability to resist moisture damage.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Moisture damage is a widespread concern among researchers and is also the main factor hindering the application of bio-asphalt in the road field. Especially in bio-regenerated asphalt, although bio-oil can restore the rheological properties of aged asphalt, it does not mean that it has a positive effect on the ability of asphalt to resist moisture damage and even makes the asphalt very susceptible to moisture damage. The moisture damage of bio-oil is usually related to its acidic component, polarizability, and water-soluble components, which leads to an increase in the moisture sensitivity of bio-asphalt, resulting in the failure of the adhesion and cohesion of the asphalt mixture . Oldham et al reduced acidic compounds in waste cooking oil through transesterification, significantly reducing its ability to resist moisture damage.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…20 Ameri et al summarized the potential effects of bio-oil produced from different biomass sources on the physical aging, chemical aging and moisture damage of asphalt. 21 Halil Durak summarized the main process parameters and technical applications of hydrothermal liquefaction, hydrothermal carbonization, pyrolysis and gasification. 22 Zhuang et al conducted a systematic comparison between direct HTL and stepwise HTL from a technical and economic perspective, and studied the transformation form of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Ameri et al. summarized the potential effects of bio-oil produced from different biomass sources on the physical aging, chemical aging and moisture damage of asphalt . Halil Durak summarized the main process parameters and technical applications of hydrothermal liquefaction, hydrothermal carbonization, pyrolysis and gasification .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews that discuss in more detail the biomass thermochemical processes to obtain bio-oil for road construction and the properties of bio-bitumen and bio-asphalt can be found in [23,24,31,32]. These reviews point out that in comparison with base bitumen, the performance of bio-bitumen can be better or worse in different temperature ranges (low, intermediate and high), and the same occurs for bituminous mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews point out that in comparison with base bitumen, the performance of bio-bitumen can be better or worse in different temperature ranges (low, intermediate and high), and the same occurs for bituminous mixtures. Ameri et al [31] showed that there is high variation among bio-oils from the same biomass source processed with different methods and that there are no established methods for evaluating and comparing the performance of bio-bitumens. Bio-oils have different chemical compounds from bitumen, and the interaction between them can increase or decrease the mobility of molecular chains at different temperatures, which affects resistance to thermal-and fatigue-cracking and rutting [32].…”
Section: Introductionmentioning
confidence: 99%